2010
DOI: 10.2165/11532550-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Paediatric Crohnʼs Disease Educational Plan

Abstract: Overall, the results of the evaluation of the Infliximab Paediatric Crohn's Disease Educational Plan were satisfactory. The objective of education of internal personnel of the pharmaceutical companies distributing infliximab was completely achieved; over 90% of physicians reported being aware of the benefits and risks of infliximab for the treatment of paediatric Crohn's disease. Further work should be carried out across all countries to educate physicians on providing patients with the infliximab Patient Aler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…For studies that involved surveys, the definition of RMI effectiveness was not explicit, consisting mainly of a change in practice (change in medication dosage or drug, referral of patients to a specialist, performance of baseline assessment before initiation of a medical treatment, etc.) ( n = 5), knowledge retention ( n = 5), awareness of RMIs ( n = 5), and increase of disclosure of information ( n = 1) . In cases where effectiveness was defined as knowledge retention, there was no specification on what represented adequate knowledge retention or what information should the target population have retained …”
Section: Resultsmentioning
confidence: 99%
“…For studies that involved surveys, the definition of RMI effectiveness was not explicit, consisting mainly of a change in practice (change in medication dosage or drug, referral of patients to a specialist, performance of baseline assessment before initiation of a medical treatment, etc.) ( n = 5), knowledge retention ( n = 5), awareness of RMIs ( n = 5), and increase of disclosure of information ( n = 1) . In cases where effectiveness was defined as knowledge retention, there was no specification on what represented adequate knowledge retention or what information should the target population have retained …”
Section: Resultsmentioning
confidence: 99%
“…The high overall level of risk awareness observed in the present study was comparable to that reported for similar studies surveying HCP risk awareness for other drugs for which additional educational materials had been distributed. 10–16 All of these studies reported risk awareness levels that generally ranged above 80%. 10–16 The two previous publications of HCP survey studies examining risk awareness for other anti-TNF-α antibodies, for which EPs had been implemented, reported very similar risk awareness levels to those observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This should include a careful history for risk factors for tuberculosis [95]. Anergy can limit the value of skin testing with PPD [92], and in vitro specific blood tests may be more sensitive and specific [96], though there is little information in children.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…This anticipatory approach should also include annual influenza vaccination, pneumococcal vaccination, human papillomavirus vaccination to young females, and hepatitis B to seronegative patients [99]. A history of malignancy is also recognised to pose a risk factor [95]. There are significant disparities between countries in the practice and extent of screening before commencing a biological in children [95].…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation